Analisa Penilaian Kinerja Fisik Bangunan Irigasi Daerah Irigasi (DI) Purworejo, Desa Tunjungtirto, Kecamatan Singosari - Ansonya Ansonya; Danang Bimo Irianto; Galih Damar Pandulu (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
Irrigation networks play a strategic role in ensuring water availability for agricultural production. This study was conducted in the Purworejo Irrigation District in Tunjungtirto Village, Singosari Subdistrict, Malang Regency, with a service area of 128 ha. The study aimed to assess the physical condition and operational functionality of the network and to determine the Irrigation System Performance Index as a basis for formulating remedial measures. The research approach involved direct field surveys combined with quantitative assessments using performance evaluation parameters for irrigation infrastructure. The aspects analyzed included the structural stability of the facilities, the operational reliability of the water gates, the smoothness of flow distribution, the level of sedimentation, and the condition of supporting facilities. The findings revealed infrastructure degradation characterized by concrete cracks, deterioration of the lining, corrosion of metal components, and sediment buildup that reduces flow capacity. Based on the calculations, the physical performance index reached 47.83%, which falls into the “severely damaged” category with a high level of functional impairment. These conditions indicate that water distribution services are not yet operating optimally. Therefore, a comprehensive rehabilitation program is needed, including structural repairs, channel cross-section normalization, replacement of control devices, and improvements to the drainage system to restore the irrigation network’s performance in a sustainable manner.